Salicylic Acid, a Plant Hormone, Suppresses Phytophagous Insect Immune Response by Interrupting HMG-Like DSP1 - Mollah, Md. Mahi Imam; Choi, Hyong Woo; Yeam, Inhwa; Lee, Je Min; Kim, Yonggyun (Frontiers in Physiology, 2021)
Salicylic acid (SA) is a plant hormone that can mediate various plant physiological processes. SA can bind to human high mobility group box 1 (HMGB1) and interrupt its role in mediating immune responses. Dorsal Switch Protein 1 (DSP1) is an insect homolog of HMGB1. In this study, a DSP1 (Se-DSP1) encoded in Spodoptera exigua, a phytophagous insect, was characterized and its potential role in immune response was explored. Upon bacterial challenge, Se-DSP1 was localized in the nucleus and released into the hemolymph. The released Se-DSP1 could mediate both cellular and humoral immune responses by activating eicosanoid biosynthesis. SA could bind to Se-DSP1 with a high affinity. Immune responses of S. exigua were significantly interrupted by SA feeding. Larvae reared on tomatoes with high endogenous SA level became more susceptible to entomopathogens. Taken together, these results suggest a tritrophic defensive role of plant SA against phytophagous insects.